Analisis SWOT sebagai Dasar Penyusunan Strategi Pengembangan Pondok Pesantren Modern Daar El-Kutub Bayah untuk Meningkatkan Keunggulan Kompetitif - Kasronudin; Rika Sa'diyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the internal and external factors of Pondok Pesantren Modern Daar El-Kutub Bayah and formulate appropriate development strategies to enhance the institution's competitive advantage amidst competition with various types of educational institutions in its surroundings. The research employs a qualitative approach with a case study type. Data were collected through in-depth interviews, participant observation, and documentation. Data analysis was conducted using SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) followed by the formulation of the TOWS Matrix to generate strategic alternatives. The findings reveal that Pondok Pesantren Modern Daar El-Kutub Bayah possesses key strengths, including its long-standing experience as an educational institution, students' commendable achievements, adequate facilities and infrastructure, and alumni who have established their own Islamic boarding schools. However, the pesantren faces serious weaknesses, including poor educational management, modest facilities, a drastic decline in student enrollment over the past five years, and ineffective internal communication patterns. Available opportunities encompass an extensive alumni network, a strategic location near tourist attractions, professional educators with high qualifications (Bachelor's, Master's, and Doctoral candidates), competitive quality, and relatively affordable educational costs (IDR 650,000 covering meals, tuition, health services, dormitory, and electricity). The primary threats arise from the presence of free public schools, community schools, integrated Islamic schools, and the community's preference for sending their children to modern pesantren located farther away. Based on the TOWS matrix analysis, four main strategies are formulated: (1) SO strategy focusing on optimizing the alumni network and strategic location; (2) WO strategy emphasizing governance improvement, enhanced internal communication, and strengthened marketing leveraging affordable costs; (3) ST strategy centered on strengthening competitive advantage based on experience, achievement, and educator quality; and (4) WT strategy involving comprehensive internal improvement, communication enhancement, and student recovery strategies. This research contributes to the development of strategic management in Islamic educational institutions, particularly modern Islamic boarding schools facing crises of trust and declining student enrollment.